PRKAA1/AMPKα1-driven glycolysis in endothelial cells exposed to disturbed flow protects against atherosclerosis - Qiuhua Yang (Nature Portfolio, 2018)
Increased glycolysis and inflammatory responses have been observed in endothelial cells exposed to disturbed flow. However, the role of endothelial glycolysis in atherosclerosis is unclear. Here the authors unveil a protective role for glycolysis by showing that endothelial deletion of Prkaa1 accelerates atherosclerosis in hyperlipidemic mice through a reduction of glycolytic metabolism.